Tinjauan Imunologi pada Fenomena Non-Responder terhadap Vaksinasi Hepatitis B: Analisis - Adika Zhulhi Arjana; Ninda Devita (Cermin Dunia Kedokteran, 2025)
Hepatitis B vaccine has been highly effective in preventing HBV infection. However, a subset of individuals fails to develop adequate protective antibodies after complete vaccination series (anti-HBs ≥ 10 mIU/mL), termed as non-responders. Non-responder phenomenon is influenced by a complex interplay of genetic, immunological, and environmental factors. This narrative review aims to delve into the immunological aspects of the non-responder phenomenon, exploring the factors influencing vaccine response, the immunological mechanisms involved, and potential approaches to managing and overcoming non-responders.